PENGARUH PENGAWASAN KEUANGAN DAERAH, AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH PADA KABUPATEN MAGELANG (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study aims to determine moderating effect of local finance supervision, local finance management accountability and local finance manajemen transparency on local government performance on Magelang Regency. The population in this study chairman, secretary the accounting/financial administration departemen staff (SKPD) in Magelang Regency, such as 31 Regional Work Unit with criteria have a minimum term of one year. This study used 98 people as respondents. The data were collected by using questionnairies. The analitycal method used in this research is descriptive quatitative analysis method. The data analysis was done by using multiple linear regression tests with testing t at a significance level of 5%. The results showed that, simultaneously at variabel the local finance supervision, accountability and transparency in the finance management have a signifinact effect on the Local Government of Magelang Regency performance. From the result simultaneous test (F Test). Partially showed the results of the supervision of the local fiance has a significant effect on the Local Government of Magelang Regency performance. Accountability in the finance management and transparency in the finance management not has a significant effect on the Local Government of Magelang Regency performance. As evidenced from the result partial test (t Test).
Keywords: Supervision; Accountability; Transparency; Performance